2016
DOI: 10.1016/j.afos.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Could whole body vibration exercises influence the risk factors for fractures in women with osteoporosis?

Abstract: ObjectiveThe aim of this study was to review the literature about the relevance of the whole body vibration (WBV) in decreasing the number of fractures in osteoporotic women.MethodsSearches were performed by three independent researchers through the PubMed and PEDro databases.ResultsOnly 0.1% of the publications with “Fracture and osteoporosis” have a relation with WBV exercise. The achievements have revealed a positive effect of this exercise in patients with risk factors for fractures like osteoporosis. Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…The established vibration frequency was 16 Hz and the displacement peak (amplitude) of 4 mm was determined by the width of the platform participants' position. The vibration time was 30 s, being a series of eight repetitions with recovery (between the repetitions) of 30 s, whit a total time of 8 min of intervention [25].…”
Section: Protocol Of the Experimental Groupmentioning
confidence: 99%
“…The established vibration frequency was 16 Hz and the displacement peak (amplitude) of 4 mm was determined by the width of the platform participants' position. The vibration time was 30 s, being a series of eight repetitions with recovery (between the repetitions) of 30 s, whit a total time of 8 min of intervention [25].…”
Section: Protocol Of the Experimental Groupmentioning
confidence: 99%
“…Parameters must be considered in the WBVE protocols [20][21][22][23][24] (e.g., frequency, peak-to-peak displacement-D, acceleration peak-a Peak , position, work and rest time and number of bout and sessions). Studies reported improvements in various clinical manifestations related to KOA after WBVE [23,25,26], including the decrease of pain levels, improvements of muscle strength and flexibility, and reduction of number of falls [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…This type of activity, which can be generated with different platforms (vertical, rotational or lateral modes) (McMillan et al, 2017) generates forces that are transferred to the weight-bearing bones of the skeleton as done by other exercise modalities (Cheung and Giangregorio, 2012). So, WBV exercises could have beneficial effects associated with bone formation and the neuromuscular and cognitive functions, reducing the risk of falls and fractures (Moreira-Marconi et al, 2016; Bemben et al, 2018). However, several authors reported conflicting results due to the variety of protocols used (Marin-Puyalto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%